Obstacle-aware routing problem in a rectangular mesh network - Adzhar, Noraziah (Hikari Ltd., 2015)
In an automatic design process for very large scale integration/printed circuit board (VLSI/PCB), routing problem is one of the most important and crucial part after components placement phase. This process is notoriously difficult, and a problem consists of a set of two-pin nets, is known to be NP-complete. In this problem, we considered a rectangular mesh network with all the location for blocks with pins on the boundaries and obstacles is predefined. Given a set of two-pin nets, our goal is to establish connections in the network by avoiding all the obstacles while satisfying the design rules. In this paper, we are using simulated annealing routing method with Dijkstra's shortest path algorithm to provide the best path for each connection if it exists. The simulation results showed that by accepting some uphill movements based on Boltzmann probability function led to better results and yield to lower energy level. This suggests the technique is suitable for adoption into real problem. © 2014 Noraziah Adzhar and Shaharuddin Salleh.